KLAUSULA BAKU TENTANG PEMBERIAN KUASA DIHUBUNGKAN DENGAN HUKUM POSITIF - Dika Ratu Marfu’atun (LPPM Universitas Bina Bangsa, 2022)
Baku Clause is any rules or conditions and conditions that have been prepared and set in advance unilaterally by business actors as set forth in a document and / or agreement that is binding and must be fulfilled by consumers. In the creation of the standard clause there are conditions that aim to provide protection to consumers and prohibit the unilateral granting of power from consumers to business actors. Some laws and regulations governing the granting of power of attorney in the standard callusula, one of which is Article 1792 of the Civil Code, Article 18 of UUPK and Article 22 of POJK Number: 1/POJK.07/2013 on Consumer Protection of the Financial Services Sector. The type of research used is normative juridical research conducted by examining library materials or secondary data that include primary legal materials, secondary legal materials and tertiary legal materials so as to obtain an overview of the standard clauses about power of attorney associated with positive law. The results showed that the granting of power is an agreement, namely the agreement of both parties. The agreement is said to be valid if it meets the conditions in accordance with Article 1320 of the Civil Code, namely agreeing, conversing, a certain thing and a halal cause, but it should not conflict with the laws and regulations namely Article 18 paragraph (1) letter d of Law No. 8 of 1999 on Consumer Protection.